New aerophytic morphospecies of Nostoc (Cyanobacteria) from São Paulo State, Brazil - Sant'Anna, Célia Leite; Azevedo, Maria Teresa de Paiva; Branco, Luis Henrique Zanini [UNESP]; Komárek, Jiří (Instituto de Botânica, 2007)
Ambientes aeroffticos brasileiros são quase totalmente desconhecidos em relação à sua flora de cianobactéria. Durante o estudo desta flora, três morfoespécies do gênero Nostoc foram encontradas em diferentes habitats do Estado de São Paulo, Brasil. Com base na morfologia, especialmente na formação e forma dos acinetos, no ciclo de vida e na ecologia, estas populações foram consideradas distintas de todos os demais taxons de Nostoc e são propostas como espécies novas: N. interbryum, N. viride, and N. alatosporum.

Brazilian aerophytic biotopes are almost completely unknown regarding to cyanobacterial flora. During the study of this special flora, three morphospecies of the genus Nostoc from different habitats in the State of São Paulo, Brazil, were found. Based on their morphology, especially by formation and shape of the akinetes, life cycles and ecology, these populations were considered distinct from all known taxa of Nostoc and are proposed as new species: N. interbryum, N. viride, and N. alatosporum.
Novas morfoespécies aerofíticas de Nostoc (Cyanobacteria) do Estado de São Paulo, Brasil
Keywords: Brasil; Cyanobacteria; espécies novas; Nostoc; Brazil; Cyanobacteria; new species; Nostoc